The World Bank research observer - World Bank (Washington,D.C World Bank, 1994)
WB elibrary": "The World Bank Research Observer is intended for anyone who has a professional interest in development, and it written to be accessible to nonspecialist readers. Contributors examine key issues in development economics, survey the literature and the latest World Bank research, and debate issues of development policy. Articles are reviewed by an editorial board drawn from across the Bank and the international community of economists. Consistency with World Bank policy is not a factor in the selection of articles. The journal welcomes editorial comments and responses, which will be considered for publication to the extent that space permits. On occasion the Observer considers unsolicited contributions"
Full text article are available from JSTOR: https://www.jstor.org/journal/worlbankreseobse
Keywords: Economic development; ECONOMIC DEVELOPMENT; DEVELOPING COUNTRIES; ECONOMIC CONDITIONS; PERIODICALS